BUSINESS MANAGEMENT AND THE CHARACTERISTICS OF INTERNATIONAL E-MARKETING AND ITS IMPACT ON THE CONSUMER - Ghufran A. Mohammed (American Journals, 2023)
Marketing: It is the processes related to planning the implementation of concepts related to pricing, promotion and distribution of ideas, goods and services in order to achieve exchanges towards satisfying individuals and meeting the objectives of the organization. Marketing Concept: It is a social process through which individuals or groups get what they need or want through exchanges between them for products and determining their values.1- Needs, Desires, and Demand Needs: They represent the basics that a person seeks in order to obtain them, such as food, clothing, protection, safety, and respect. Desires: They represent wishes that the individual desires to be fulfilled, depending on the environment in which he lives. Demand: It represents the quantity required by individuals of a particular good or service. during a specified period of time. 2- Products, services and expertise Products: the consumer seeks to achieve the best benefits in exchange for the money he paid in order to obtain them. Experience: It is the experience that the marketer possesses to achieve distinction and creativity from other producers or marketers. 3- Value, Cost and Satisfaction Value: Examples of it include a person who wants to move from his place of residence to his place of work by means of transportation such as bicycle, taxi, bus, but he will set a number of criteria that distinguish one unit from another. Satisfaction wants it: it represents the results achieved from the use of that product exclusively, and it does not have to be what is less expensive than others. 4 - Exchange and Relationships Individuals can satisfy their needs or desires through exchange Q / What are the conditions that must be achieved in the realization of the marketing exchange process? C / 1- The presence of at least two parties in the exchange process 2- Each party owns something and this may be of value to the other party 3- Each party has the ability to communicate and deliver